2019
DOI: 10.1021/acsabm.9b00892
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Crowding and Confinement Effect on the Growth of DNA Nanotubes in Dextran and Hyaluronic Acid Media

Abstract: The dense medium modulates the molecular structure and bioreactions in living cells via both noncovalent interactions and macromolecular crowding and confinement effects. However, the interplay between the volume effect and noncovalent interactions remains unclear. In this work, we studied in detail on how electrostatic interactions influence the crowding and confinement effect by comparing the formation and elongation of DNA nanotubes in branched dextran and charged hyaluronic acid (HA) solution of a broad co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Typically, these molecules occupy a huge volume of the cell (up to 40%), equivalent to a concentration of up to 400 mg/mL ( Fulton, 1982 ; Zimmerman et al, 1991 ). Two terms can be encountered in the literature: “macromolecular crowding” referring to dynamic effects of volume exclusion encountered between two molecules and “macromolecular confinement” referring to the same effect caused by the static shape and size of the system ( Huan-Xiang et al, 2008 ; Sanfelice et al, 2013 ; Zhang et al, 2019 ). Both describe a typical free-space limitation occurring in a highly concentrated environment of molecules which leads to non-specific interactions between macromolecules in close proximity ( Sarkar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these molecules occupy a huge volume of the cell (up to 40%), equivalent to a concentration of up to 400 mg/mL ( Fulton, 1982 ; Zimmerman et al, 1991 ). Two terms can be encountered in the literature: “macromolecular crowding” referring to dynamic effects of volume exclusion encountered between two molecules and “macromolecular confinement” referring to the same effect caused by the static shape and size of the system ( Huan-Xiang et al, 2008 ; Sanfelice et al, 2013 ; Zhang et al, 2019 ). Both describe a typical free-space limitation occurring in a highly concentrated environment of molecules which leads to non-specific interactions between macromolecules in close proximity ( Sarkar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…If dextran is added into water‐in‐oil‐droplets alongside the DNA‐motifs for printing, we obtained a more slender cone in the z ‐dimension of roughly half the thickness seen for printing without dextran (Figure S7 and Video S3, Supporting Information). Moreover, less off‐target polymerization was observed likely due to the crowding effects or an increase in viscosity slowing down diffusion [ 42 ] (Figure S7 and Video S3, Supporting Information). The addition of dextran did not seem to alter the results achieved for the erasing of the DNA hydrogel (Figure S7 and Video S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The depletion force is a force with an entropic origin often seen in macromolecular crowding environments that manifest in polymer solutions, favoring the self-assembly of biopolymers (Marenduzzo et al, 2006), and which can stabilize the DNA duplex (Nakano et al, 2004;Hong et al, 2020). The assembly of DNA tile microtubes (Zhang et al, 2020) and compacting genomic DNA (Zhang et al, 2009) under macromolecular crowding conditions have also been reported. In Figure 2, the dextran concentration in the dextran phase in both the single-and two-phase systems was the same; however, the dextran droplets in the two-phase systems contained a small amount of PEG molecules.…”
Section: Discussionmentioning
confidence: 99%